2019
DOI: 10.1016/j.ssmph.2019.100404
|View full text |Cite
|
Sign up to set email alerts
|

Methods of measuring associations between the Retail Food Environment and weight status: Importance of classifications and metrics

Abstract: Despite considerable research, evidence supporting associations between the ‘Retail Food Environment’ (RFE) and obesity remains mixed. Differences in the methods used to measure the RFE may explain this heterogeneity. Using data on a large (n = 10,111) sample of adults from the Yorkshire Health Study (UK), we modelled cross-sectional associations between the RFE and weight status using (i) multiple definitions of ‘Fast Food’, ‘Convenience’ and ‘Supermarkets’ and (ii) multiple RFE metrics, identified in a prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 62 publications
2
50
0
Order By: Relevance
“…Conclusion: There is some indication that neighbourhood greenspace is related to physical activity. However, in agreement with other literature 26,27 , this study shows different definitions of environment can produce different results. Future work must use measures that are relevant, consistent and transferable.…”
Section: Methods and Resultssupporting
confidence: 91%
“…Conclusion: There is some indication that neighbourhood greenspace is related to physical activity. However, in agreement with other literature 26,27 , this study shows different definitions of environment can produce different results. Future work must use measures that are relevant, consistent and transferable.…”
Section: Methods and Resultssupporting
confidence: 91%
“…Although a recent Australian study noted “ratio-based measures of healthy to unhealthy food stores have been rarely investigated” ( [ 48 ] p.103), it appears that the use of ratio and proportion measures are in fact prominent in the food environment field with a full systematic search of the literature likely to reveal even more studies than those already cited in this debate. Whilst it is fully acknowledged that measures are needed that capture the mix of food retail stores available, recent calls to advocate for ratio and proportion measures may be misguided [ 7 , 26 , 41 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is recognised that some (not all) of the issues raised hold true for absolute quantity measures. However, one of the unique points about ratio and proportion measures is that they are advocated for as an advance on absolute quantity measures and often viewed as being more sophisticated [ 26 , 51 , 52 ]. As demonstrated, this is potentially not the case and thus this debate paper makes an important contribution to the literature by highlighting these issues with the aim of redirecting the collective focus of this field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was shown that people do not shop for food in their immediate neighborhood but will instead travel great distances to the supermarket or fast food restaurant of choice . Third, the choice of BE variables can influence the magnitude and direction of the observed association between BE and health; not all such metrics are predictive of health . Relatedly, investigators should be more transparent regarding the variables and methods used to quantify the BE .…”
Section: Evolving Measures Of Be Exposurementioning
confidence: 99%